Low Glycemic Index Taro Tuber (Colocasia esculenta L.) Flakes as Alternative Food Product for Diabetes Management - Sultan, Asriana; Rinaldi, Rinaldi; Sulaiman, Sri Sulistiana; Aanisah, Nuur; Khumaidi, Akhmad; Bahar, Zulhaerana; Syamsidi, Armini (Sciences of Pharmacy, 2025)
Flakes are a type of instant food product commonly consumed as a breakfast alternative, especially those labelled “low-glycaemic index” can be suitable for individuals with diabetes. Taro tubers (Colocasia esculenta L.) containing high fibre and low fat are among the raw materials that can be processed into instant food. Therefore, this study aimed to develop and determine the glycaemic index (GI) of Taro tuber flakes as an alternative processed food product for individuals with diabetes. Three distinct formulas, namely F1, F2, and F3, were developed with varying drying temperatures of 40 °C, 60 °C, and 80 °C. These were comprehensively evaluated through sensory testing (hedonic and scoring), followed by the analysis of moisture content, ash content, microbial examination, and glycaemic index. The results showed that all three developed formulas F1, F2, and F3 xhibited low glycaemic index values (below 55), along with acceptable moisture and ash content, and were free from Escherichia coli and Salmonella typhi contamination. Among them, F2, which was dried at 60 °C, showed the lowest glycaemic index value of 15.1, indicating its potential to produce a minimal postprandial blood glucose response. Furthermore, F2 received an average hedonic score of 6, which indicates favorable sensory acceptance in terms of taste, color, texture, and aroma. Therefore, F2 was selected as the most suitable formula that can be consumed as an alternative food product to help manage diabetes through low-GI dietary strategies.